2016
DOI: 10.5430/ijfr.v8n1p172
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Fluctuations and Their Impact on Stock Market Returns in Jordan: Evidence from an Asymmetric Cointegration Analysis

Abstract: This paper examines whether Amman stock market returns responds asymmetrically to oil price fluctuations for the quarterly period 2000-2015 by applying asymmetric cointegration. Using both TAR and MTAR specification of Enders and Siklos’s (2001) models, and based on the asymmetric ECM, the results provide evidence that stock returns react to oil price variations in an asymmetric manner. In particular, rising oil prices has a larger impact on stock returns; this implies that increases in oil prices have a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Its prices have shown great instability in recent times, caused by economic, financial and geopolitical factors. The variations in its prices have a great impact on the overall economy, inflation, the exchange rate, corporate earnings, and other economic variables due to its extensive use as a crucial input in the production process, and as a final consumption good (Muhtaseb andAssaf, 2017and Aggarwal andSaqib, 2017). A considerable volume of work has emerged examining the connections between oil price shocks and stock returns and between oil price shocks and stock market volatility (Kang et al, 2015;Lee et al, 2017;Aggarwal and Saqib, 2017;Smyth and Narayan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Its prices have shown great instability in recent times, caused by economic, financial and geopolitical factors. The variations in its prices have a great impact on the overall economy, inflation, the exchange rate, corporate earnings, and other economic variables due to its extensive use as a crucial input in the production process, and as a final consumption good (Muhtaseb andAssaf, 2017and Aggarwal andSaqib, 2017). A considerable volume of work has emerged examining the connections between oil price shocks and stock returns and between oil price shocks and stock market volatility (Kang et al, 2015;Lee et al, 2017;Aggarwal and Saqib, 2017;Smyth and Narayan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…And it had significant power for forecasting the GDP (Campbell et al, 2001;Levine & Zervos, 1998). In line with that, Muhtaseb and Al-assaf, (2017) concluded that stock market volatility positively and significantly affected emerging economics in developing financial markets rather than in developed economics.…”
Section: -Literature Review and Theoretical Developmentmentioning
confidence: 57%
“…The literature in the field informed the selection of the cointegration techniques with studies investigating the long-run association among stock markets and oil prices with an interest in the GCC nations (Bouri et al, 2016;Chau et al, 2014;Imarhiagbe, 2010;Miller & Ratti, 2009;Arouri & Fouquau, 2009;Granger et al, 2000). Other researchers have developed studies testing cointegration among stock prices and oil prices in a broader context, like, for example (Muhtaseb & Al-Assaf, 2017;Bahmani-Oskooee & Saha, 2015;Asteriou & Bashmakova, 2013;Constantinos et al, 2010). These researches offer new evidence on the significance of the specific econometric models, and as such, they contribute to ensuring that the selected research framework to support this study is appropriate.…”
Section: Testing For Long-run Dynamicsmentioning
confidence: 99%